2017
DOI: 10.1002/er.3955
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics study on the generation of hydrogen from an aluminum/water system using synthesized aluminum hydroxides

Abstract: Summary Kinetics study on the generation of hydrogen from an Al/water system is performed. The reaction is affected by three major factors such as the concentration of hydroxyl ions (pH values), catalysts, and temperature. However, these factors are interacted and sometimes difficult to separate. This study demonstrates how these factors affect the generation of hydrogen in an Al/water system. Aluminum hydroxide, Al(OH)3 (bayerite phase), synthesized using a chemical solution method, is proved to be a very eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The twisting and bond stretching frequency for gibbsite phase hydroxyl groups are at 3617, 3525 and 3085 cm −1 . The absorption bands at 3085 cm −1 are differentiated perpendicular to the (001) planes and the bands at 3617 and 3525 cm −1 are polarized in this plane, which is the corresponding gibbsite phase bond 36‐40 . The bayerite (S. No.1) has four absorption bands at 3658, 3556, 3482 and 3414 cm −1 for O‐H bonding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The twisting and bond stretching frequency for gibbsite phase hydroxyl groups are at 3617, 3525 and 3085 cm −1 . The absorption bands at 3085 cm −1 are differentiated perpendicular to the (001) planes and the bands at 3617 and 3525 cm −1 are polarized in this plane, which is the corresponding gibbsite phase bond 36‐40 . The bayerite (S. No.1) has four absorption bands at 3658, 3556, 3482 and 3414 cm −1 for O‐H bonding.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption bands at 3085 cm −1 are differentiated perpendicular to the (001) planes and the bands at 3617 and 3525 cm −1 are polarized in this plane, which is the corresponding gibbsite phase bond. [36][37][38][39][40] The bayerite (S. No. 775 cm −1 , 624 cm −1 , 518 cm −1 , and 426 cm −1 (S.No.1), 673 cm −1 , 487 cm −1 and 426 cm −1 (S.No.4) belong to the AlO 6 vibration mode.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…[1][2][3][4][5] There are various hydrogen production technologies including catalytic reforming, water electrolysis, water photolysis, biomass, metals, metal hydride, and so on, with all of them having their advantages and disadvantages. [6][7][8][9][10][11][12][13][14][15] For example, production of hydrogen from the fossil fuels though has high production efficiency, cannot be used as a long-term strategy for hydrogen economy due to its un-sustainability and airpollution; consumption of large quantity of electricity has made water electrolysis unfavorable though it can yield high-purity hydrogen; hydrogen production from the biomass, though is difficult to control with very low efficiency [16][17][18] but it is a promising method for the future. Ability to solve the problem of hydrogen storage and transportation has led to increasing attention being paid to the in-situ hydrogen generation via the reaction of metals (Al, Mg, Li, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The reaction rates and yields were optimized using Al(OH) 3 synthesized from Al (NO) 3 , given the high surface area and sharp edge of the hexagonal Al (OH) 3 crystals . The activation energy of the Al/water reaction was reduced from 158 kJ/mol to about 75 kJ/mol with the Al (OH) 3 catalyst . It was suggested that the addition of Al (OH) 3 , γ‐Al 2 O 3 , or α‐Al 2 O 3 helps dissociate the water molecules on the surface of these oxides and promotes the hydration of the oxide film on aluminum particles .…”
Section: Introductionmentioning
confidence: 99%
“…25 The activation energy of the Al/water reaction was reduced from 158 kJ/mol to about 75 kJ/mol with the Al (OH) 3 catalyst. 26 It was suggested that the addition of Al (OH) 3 , γ-Al 2 O 3 , or α-Al 2 O 3 helps dissociate the water molecules on the surface of these oxides and promotes the hydration of the oxide film on aluminum particles. 27 On the other hand, adding Na 2 CO 3 reduces the activation energy of low-temperature Al/H 2 O reaction (60°C-80°C) from 74.49 kJ/mol (without additive) to 43.03 kJ/mol (with 5-wt% Na 2 CO 3 addition).…”
Section: Introductionmentioning
confidence: 99%